2002
DOI: 10.1038/sj.gene.6363923
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the association of human BLYS (BAFF, TNFSF13B) polymorphisms with systemic lupus erythematosus and rheumatoid arthritis

Abstract: Recent studies indicated a substantial role of BLyS (BAFF, TNFSF13B) in the pathogenesis of systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) in humans and in animal models. This study was conducted to screen for polymorphisms of human BLYS, and to examine whether they are involved in the genetic susceptibility to human SLE and RA. A systematic polymorphism screening was performed in the coding region, 5 0 and 3 0 untranslated regions, and promoter region of human BLYS. Association of the detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 33 publications
4
72
1
1
Order By: Relevance
“…Weak associations with certain SNPs did not remain significant after correction for multiple testing, although associations with selected ethnicities and/or subgroups of SLE patients were identified (24). Those findings bring to mind the lack of genetic associations observed for SLE and gene polymorphisms of BLyS (25,26), a proinflammatory cytokine that, like leptin, is elevated in SLE, promotes SLE in mice and in humans (27), and is targeted for therapy in certain SLE patients (28).…”
Section: Discussionmentioning
confidence: 96%
“…Weak associations with certain SNPs did not remain significant after correction for multiple testing, although associations with selected ethnicities and/or subgroups of SLE patients were identified (24). Those findings bring to mind the lack of genetic associations observed for SLE and gene polymorphisms of BLyS (25,26), a proinflammatory cytokine that, like leptin, is elevated in SLE, promotes SLE in mice and in humans (27), and is targeted for therapy in certain SLE patients (28).…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with the results of their study, our findings revealed that primary immunodeficiency patients, including those with CVID, IgAD and XLA, showed increased plasma levels of BAFF and APRIL. It was suggested that primary antibody deficiency might have common immunological features such as monocyte activation (24)(25)(26)(27). It has been reported that inflammation and cytokines such as IFNγ or G-CSF in particular enhance BAFF production (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…49 Thus, it is possible that this SNP may change the binding affinity of MZF1. 47 Further functional studies are necessary to clarify this possibility. Encouraging these studies is the fact that increased BLYS level was also observed in the serum or synovial fluid of human SLE, rheumatoid arthritis (RA) and Sjögren's syndrome.…”
Section: Expression Of Cd40l On T Cells Is Transient With the Ligandmentioning
confidence: 99%
“…A tendency for increase of the BLYS À871 T/T genotype was observed in a subgroup of SLE patients with anti-Sm antibodies and the BLYS mRNA level was significantly elevated in the monocytes from individuals having the À871T allele. 47 Elevated BLYS levels correlated with the presence of À871T was observed in patients with familial B-cell chronic lymphocytic leukemia as well. 48 The position À871 is located in the binding site of transcription factor MZF1, which was reported to be preferentially expressed in differentiating myeloid cells.…”
Section: Expression Of Cd40l On T Cells Is Transient With the Ligandmentioning
confidence: 99%
See 1 more Smart Citation